Cultural using in Abu-Tmam Poetry - علي عبد علي كريم (Al-Adab Journal, 2018)
This study discusses the cultural uses in the poetry of Abu Tammam that has widened and lengthened branched out to all the cultures of the ancient Arab squeezed from the (hair, news, and lineages), and religious, as it relates to them did not call superficial. It was a telephone profoundly accurate Insider cruised Abu Tammam of cultural heritage inventory in his mind and thought, it is in all cases, has built a literary architecture on this rich background in a manner conveying meaning, and strengthens, and even enable him to say what they cannot say Asraha, so Batca a heritage symbol (literary or religious), or a historical event, enabled him to carve his vocabulary, and his words and how to cast into molds have my choice So tried this study to detect the source of inspiration for the creative experience, including the availability of the connotations and overtones leaked from those ancient texts (poetry and prose), history, and legends in a special systems of technical features, and aesthetic; to become his text present, and future, is seen as in their own natural environment, to become a manifestation of the merger, and cultural interaction, Vtvaal texts are conjured from memory - inside text-form harmonious units in the structure of the text carrier between the sides elements excitement, by the imagination which creates a whole new world contrary to the past Almighty texts indicate this fact (interaction), which prompted the researcher to walk to decode the new structure threading, and try to return them to their origins and stand on the way in which the fusion and interaction and the process of building the new text.